The effects of positive emotion and bonus packs in encouraging impulse buying - Anshori, Asroful Adim; Holik, Asep Epriana Nur; Fatimah, Siska Ernawati; Srisuk, Prattana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The impact of good emotions and bonus pack promotion tactics on impulsive shoppers in retail establishments, specifically at Indomaret and Alfamart in Cirebon, was investigated in this study using a quantitative methodology. The research population consisted of 399 individuals aged between 19 and 24, drawn from 263,781 people. The sampling formula used was Slovin's formula, and the samples were selected randomly. The research hypothesis was tested using random sampling based on Slovin's formula. The study results indicate that positive emotions and bonus packs affect the desire to purchase at Indomaret and Alfamart stores. The primary effect is that bonus packs encourage impulsive buying. This is because bonus packs provide immediate added value to consumers, such as additional products or discounts to enhance appeal and purchase interest. These findings offer insights and strategic guidance for retail businesses in designing marketing strategies, particularly targeting students. Such strategies may include a combination of attractive bonus pack promotions and creating a pleasant shopping experience to encourage impulse buying and enhance customer loyalty.